Application of the 2021 AAPOS Guidelines in Clinics with Revision and Validation of SPOT Referral Criteria - Li R; Yan Q; Lin X; Wu Z; Zhu H; Guo W; Zhang P; Zuo F; Wu Z; Liu H; Huang D (Clinical Ophthalmology)
Rui Li,1,* Qi Yan,2,* Xiao Lin,3,* Zhujian Wu,4 Hui Zhu,4 Wei Guo,4 Peibin Zhang,4 Feidi Zuo,5 Ziyan Wu,5 Hu Liu,4 Dan Huang4 1Department of Ophthalmology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People’s Republic of China; 2Department of Ophthalmology, Children’s Hospital of Soochow University, Suzhou, People’s Republic of China; 3Department of Ophthalmology, Baylor College of Medicine, Houston, TX, USA; 4Department of Ophthalmology, the First Affiliated Hospital with Nanjing Medical University, Nanjing, People’s Republic of China; 5The Fourth School of Clinical Medicine of Nanjing Medical University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hu Liu; Dan Huang, Department of Ophthalmology, The First Affiliated Hospital with Nanjing Medical University, Nanjing, 210029, People’s Republic of China, Tel +86 (25) 68136470, Fax +86 (25) 83275171, Email liuhu@njmu.edu.cn; huangdan@njmu.edu.cnPurpose: This study aims to validate and revise the Spot Vision Screener referral criteria for detecting amblyopia risk factors (ARFs), visually significant refractive error (VSRE), and amblyopia.Methods: In clinics, we gathered data from children aged 12 months to 7 years. The validity of the cut-off values was assessed using receiver operating characteristic (ROC) curves, with cycloplegic retinoscopy serving as a reference. These results were compared to the age-based 2021 AAPOS diagnostic thresholds. Additionally, this study validated previously reported referral criteria within its population.Results: The study involved 1103 children (347 below four years; 756 aged four years and above). We established optimal cut-off points for hyperopia, myopia, astigmatism, and anisometropia: +2.13D, − 2.88D, − 2.88D, and 0.88D for children under four years; +1.88D, − 1.88D, − 2.13D, and 0.88D for those four years and older, forming the “Nanjing Referral Criteria”. The Youden index for several existing referral criteria ranged from 0.08 to 0.53 in detecting ARFs & VSRE and from 0.08 to 0.48 for ARFs, VSRE, and amblyopia.Conclusion: The study proposes the “Nanjing Referral Criteria” and its modified version with enhanced specificity for the Spot Vision Screener to optimize vision screening in children. Vision screening programs can utilize this validated data to select referral criteria best suited to their local context.Keywords: AAPOS guidelines, vision screening, referral criteria, the spot vision screener